Model Promosi Pada Simpanan Berhadiah Dalam Meningkatkan Kuantitas Anggota di Baitul Maal wa Tamwil - Kharis Fadlullah Hana; Ocvi Wijayanti (Jurnal Rekoginisi Ekonomi Islam, 2022)
Currently, competition for Islamic microfinance institutions is getting tougher. Various ways are done to attract customers' interest. However, some institutions still have not found the right promotion model. The purpose of this scientific research, the researcher explores the promotion model carried out by management to increase the quantity of members at BMT Mubarakah Kudus. After conducting a series of studies using systematic and measurable qualitative descriptive research methods, the following data can be obtained: the segmentation carried out by BMT is geographic segmentation, situation and use and benefits. The targeting carried out by BMT Mubarakah has been adjusted to the target market and positioning has also been carried out by BMT, so that by carrying out these three promotional models it can increase the quantity of deposit members with prizes at BMT Mubarakah. With this promotion model, there are several members who have savings accounts with prizes of more than 5 accounts, so the more accounts they have, the greater the opportunity for these members to get prizes drawn at the end of the period.